1997
DOI: 10.1111/j.1432-1033.1997.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Binding and Catalysis by L‐arginine: Glycine Amidinotransferase — A Mutagenesis and Crystallographic Study

Abstract: L-Arginine:glycine amidinotransferase catalyzes the committed step in the biosynthesis of creatine. Eight active-site mutants, D170N, D254N, H303V, D305A, R322E, S355A, C407S, and C410A of recombinant human L-arginine :glycine amidinotransferase were prepared by site-directed mutagenesis and enzymatically characterized. The crystal structures of the three mutants D170N, D254N, and C407S have been determined at 0.28-nm, 0.29-nm and 0.236-nm resolution, respectively. The mutation of active-site residues which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
(39 reference statements)
2
15
0
1
Order By: Relevance
“…When Ser247 was replaced with Met in CyrA (S247M), an increase in T opt (Table 1) was observed, indicating a more stable active site. The sulfur atom of Met302 in h‐AGAT participates in a hydrogen‐bonding network with water molecules, and is essential for stabilization of the active site in h‐AGAT [8]. Therefore, the introduction of Met at this position in CyrA could have led to a similar stabilizing hydrogen‐bonding network as in h‐AGAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Ser247 was replaced with Met in CyrA (S247M), an increase in T opt (Table 1) was observed, indicating a more stable active site. The sulfur atom of Met302 in h‐AGAT participates in a hydrogen‐bonding network with water molecules, and is essential for stabilization of the active site in h‐AGAT [8]. Therefore, the introduction of Met at this position in CyrA could have led to a similar stabilizing hydrogen‐bonding network as in h‐AGAT.…”
Section: Discussionmentioning
confidence: 99%
“…This lid structure is formed by the loop composed of residues 298–302 (300‐flap) and helix 9 [10]. Asn300 and Met302 were also found to play a role in substrate binding and stability of the active site [8,10]. These two residues are conserved in all other known AGATs except CyrA.…”
Section: Introductionmentioning
confidence: 99%
“…One possible exception is A. thaliana AgD, where a core Cys mutation reduces activity by less than 10-fold, which suggests a possible alternative role for the core Cys or a different nucleophile [32]. The role of the core His as an acid-base catalyst is also supported by structural and mutagenic studies in ADI [8,20,26], DDAH [9,23], PAD4 [15] and AGAT [33] Solvent isotope and pH rate profiling studies with PAD4 inactivators have suggested that proton donation is important for stabilization of the tetrahedral intermediate during inactivation, implying that a similar mechanism could occur during normal catalysis [34]. …”
Section: Pentein Catalysismentioning
confidence: 99%
“…Computational studies with PAD4 have suggested that a protonated Cys is energetically more favorable than a Cys thiolate in the Michaelis complex [38,39]. In addition, the core Cys residue in AGAT is also proposed to be predominantly protonated in the resting state, possibly activated by Asp305 for attack [33]. These three proposals for Cys protonation state can be summarized and linked by a thermodynamic box (Fig.…”
Section: Pentein Catalysismentioning
confidence: 99%
“…AT exhibits a rather broad substrate specificity and can utilize a wide variety of amidino donors, such as L-canavanine, 4-guanidinobutyrate, 3-guanidinopropionate, and hydroxyguanidine, and amidino acceptors, such as L-canaline, 4-aminobutyrate, 3-aminopropionate, and hydroxylamine, in addition to the physiological substrates (1). Biochemical data suggested a ping-pong mechanism for the transamidination reaction (18,19), including a transient covalent attachment of an amidino group to Cys 407 (20 -22). The crystal structure of human AT at high resolution revealed that the nucleophilic Cys 407 is located at the bottom of an narrow active site channel (23).…”
mentioning
confidence: 99%